A Community-Level Analysis of Sources and Rates of Technological Variation in the Microprocessor Market - Wade, James B. (Academy of Management Journal, 1996)
This research sought to identify the sources and rates of technological variation in an industry using a community-level framework. Using data on all merchant producers of microprocessors from 1971 to 1989, I found that new entrants were the sources of most new designs. The rate at which design sponsors entered the market follows organizational ecology's density-dependence model. Further, increasing market concentration increased the entry rate of new firms, most of which sponsored architectural innovations, suggesting that the emergence of a dominant design may paradoxically promote new approaches and technologies.